Efek Penggunaan Produk Perawatan Gigi Dan Mulut Yang Dijual Bebas (Otc) Pada Mukosa Oral - Riani Setiadhi (Jurnal Material Kedokteran Gigi, 2018)
Over-the-Counter (OTC) drug is a drug which is sold freely in the market and can be purchased without a prescription. Special markings on the packaging and etiquette of OTC drug is a green circle with a black edge. Over-TheCounter (OTC) Dental Care Products are dental care products sold directly to consumer without a prescription from the dentist. Nowadays, there has been a significant increase in the number of OTC products in the market for oral health such as mouth washes, breath fresheners, tooth whitening, tooth paste, denture cleaners etc. To find out the effect of inappropriate use of OTC dental care products on the oral mucosa. Many OTC dental products are freely sold, make easier for people to obtain the desired products without visiting the dentist. Besides those advantage, they may also cause undesirable effects due to the inappropriate use and indications which could actually risk the oral health of patients. Side effects that may occur in the oral cavity including altered taste, tooth staining, burning sensation, gingival irritation, desquamation, erosion, numbness and dryness of the oral mucosa. Discontinuing the use of these products usually will recover the oral mucosa conditions. The inappropriate use and indications of OTC dental care products could cause unwanted side effects.